A longitudinal evaluation of food safety knowledge and attitudes among Ontario high school students following a food handler training program. (June 2017) - Majowicz, Shannon E.; Hammond, David; Dubin, Joel A.; Diplock, Kenneth J.; Jones-Bitton, Andria; Rebellato, Steven; Leatherdale, Scott T.
Abstract: Youth are a unique audience for food safety education, in part due to low food safety knowledge. Although the effectiveness of such education has been explored for primary school and college students, no studies have assessed effectiveness among high school students specifically. We conducted a longitudinal intervention study in Ontario, Canada, between February and May 2015, to measure the baseline food safety knowledge and attitudes of high school students (n = 119; from 8 classes in 4 high schools), and determine whether these factors improved following in-class delivery of a provincial standardized food handler training program. Linear mixed effects regression models were used to model within-student changes in knowledge scores and attitudes over time (i.e., circa 2 and 12 weeks post-intervention), and to investigate associations with student characteristics. At baseline, knowledge and attitudes were poor. Following training, overall knowledge was significantly greater than at baseline, although at three months post-intervention only knowledge of safe times and temperatures for cooking and storing food remained significantly higher than baseline. Following training, students were significantly less interested in learning about how to avoid foodborne disease. Other attitudes, as well as knowledge of cross-contamination prevention and disinfection procedures, remained unchanged. These findings suggest that delivering existing food handler training programs within high schools may be a feasible mechanism for food safety educators to improve students' food safety knowledge, both overall and specific to safe times and temperatures, albeit potentially for short timeframes. Whether knowledge continues to decline beyond three months after training bears further investigation. As well, future research to investigate how students' actual food safety practices may change following such training, and whether improvements in knowledge translate into reduced foodborne disease risk, is warranted. Highlights: High school students have poor food safety knowledge. 2 weeks post-food handler training knowledge improved, but attenuated 3 months later. Before training, students were interested in learning about food safety. Interest in learning about food safety declined post-training. High school students do not see foodborne disease as a personal threat.